Transnational Smuggling of Migrant Workers from International Law Perspective - Ni Nengah Adiyaryani; I Putu Rasmadi Arsha Putra (Faculty of Law Universitas Lampung, 2023)
Migrant worker smuggling is a transnational organized crime that harms countries of origin, transit, and destination countries. The smuggling of migrant workers in Southeast Asia, from Southeast Asia and heading to Southeast Asia is largely due to economic factors that cause the Immigration of workers to more economically advanced countries. Weak regulations and restrictions on border control and law enforcement also exacerbate this. The scope of this research regards international legal provisions related to migrant worker smuggling as an organized transnational crime and the legal obligations of each country, which becomes the object of migrant worker smuggling against smuggling based on an international legal perspective. This type of research uses a case approach and statutory normative legal research. Primary, secondary, and tertiary legal materials were used as legal material, then compiled for analysis to answer legal problems. The results of the research, which are findings related to the legal provisions of migrant worker smuggling as a transnational organized crime, are the United Nations conventions ratified by United Nations members, one of which is the United Nations Convention Against Transnational Organized Crime (UNCATOC). Migrant workers are carrying out cooperation capacity building along the smuggling route to sharpen data to obtain a more accurate picture of the situation at home, in the region, and globally.